Increasing Knowledge About the Wound Healing Process at the Internal Medicine Clinic of Dr. Hospital. Moewardi Surakarta - Sukma, Arda Maharani; Rahmawati, Erlina; Dewi, Mustikasari; Hermawati, Hermawati; Purwanti, Sri (CV. Rayyan Dwi Bharata, 2025)
The wound healing process in patients who were observed for one week showed that 99 cases of patients had experienced a wound healing process that was appropriate to the process, 31 cases of patients experienced an extension of the wound healing process due to various different factors, and 42 cases of patients experienced an infected wound condition. The patient is able to explain the process of good wound healing, is able to explain correct wound care, is able to explain good nutritional intake. The implementation method used is health education regarding the wound healing process, good wound conditions, good nutritional intake. It was found that there were differences in the level of knowledge about the wound healing process and the correct way to care for wounds between the pre-test and post-test. This shows that there is an increase in knowledge among the audience after health education is carried out. This is evidenced by the difference in the level of knowledge during the pre-test and post-test, having the ability to apply correct wound care, to avoid infection, being able to know which wound care is appropriate to the patient's needs so as to prevent infection in the wound.